A DEEP DIVE INTO GRADUATE STUDENTS’ SELF-EFFICACY AND ACADEMIC INTERACTION IN ONLINE LEARNING - Anas, Ismail; Nur, Sahril; Afdaliah, Afdaliah; Irmawati, Irmawati; Akhmad, Akhmad (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
Research into self-efficacy has received widespread recognition in the literature. However, little study has been done on students’ self-efficacy in asynchronous online academic interactions. This study examined graduate students’ self-efficacy in regulating their online interaction strategies. Grounded in the Asynchronous Online Self-Regulated Learning Inventory (AOSRLI), the study employed a virtual case study using an online self-assessment survey and focus group interview. Seventy-eight English education master students from two universities were approached and agreed to participate in the study. As a result, the study highlighted several critical findings: 1) lack of confidence in online interaction with the professors, 2) closed-mindedness to criticism, 3) self-fanaticism, and 4) the need for self-dialoguing and self-navigation. The students were commonly inactive, indifferent, and demotivated in their asynchronous online interactions, thus creating ineffective learning communication among them. Self-regulated learning cannot grow alone and rely on the students’ in-person learning initiatives, whereas they need pedagogical imperatives to scaffold their questioning, responding, and critiquing skills. The study suggests improving teachers’ scaffolding strategies and building students’ online community of practice to promote their activeness, engagement, and participation. The implication of this study calls for the inclusion of asynchronous virtual interaction skills into online learning pedagogy and CALL teacher education.